2011
DOI: 10.1063/1.3593487
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial mixing during annealing of zinc oxide nanoparticle junctions

Abstract: The process of forming a junction between crystalline zinc oxide (ZnO) nanoparticles during pulsed thermal annealing in liquid tetradecane is studied using molecular dynamics simulation. Pairs of equal and unequal size particles are considered with emphasis on neck growth and atom mixing. The contact area and interface width of the junction are found to increase with heat pulse power albeit at different rates. The results suggest that it is possible to increase the junction area without significant mixing of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…On the other hand, as it was previously mentioned, it is inferred that a considerable reaction between the nanoparticles and the melted silica-based of the core occurs during fiber drawing in the interval 1950 °C < T ≤ 2000 °C, which causes the growth of some cubic-shaped nanoparticles up to ∼180 nm (Figure e). It is worth noticing the decrease in the number of the smallest nanoparticles, between 20 and 30 nm, in the fiber core as temperature increases (see histograms of Figure c–e), which is logical considering that the melting temperature scales with the material dimensions . Therefore, taking into consideration this observed behavior, it is suggested that the smallest nanoparticles start to be dissolved as temperature increases and react with the existing bigger nanoparticles which causes the increase of particle size due to that compositional enrichment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, as it was previously mentioned, it is inferred that a considerable reaction between the nanoparticles and the melted silica-based of the core occurs during fiber drawing in the interval 1950 °C < T ≤ 2000 °C, which causes the growth of some cubic-shaped nanoparticles up to ∼180 nm (Figure e). It is worth noticing the decrease in the number of the smallest nanoparticles, between 20 and 30 nm, in the fiber core as temperature increases (see histograms of Figure c–e), which is logical considering that the melting temperature scales with the material dimensions . Therefore, taking into consideration this observed behavior, it is suggested that the smallest nanoparticles start to be dissolved as temperature increases and react with the existing bigger nanoparticles which causes the increase of particle size due to that compositional enrichment.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noticing the decrease in the number of the smallest nanoparticles, between 20 and 30 nm, in the fiber core as temperature increases (see histograms of Figure 1c−e), which is logical considering that the melting temperature scales with the material dimensions. 24 Therefore, taking into consideration this observed behavior, it is suggested that the smallest nanoparticles start to be dissolved as temperature increases and react with the existing bigger nanoparticles which causes the increase of particle size due to that compositional enrichment. The proximity of nanoparticles to each other for the lowest drawing temperatures eases this phenomenon as temperature increases, with mass transport being a thermally activated process.…”
Section: Microstructural Characterization Of the Nanoparticle-doped S...mentioning
confidence: 99%
“…All NPZnO layers were coated by spin-coating method at 2000 rpm and then dried for 10 min at 70°C in air condition. In addition, to obtain different-sized NP-ZnO by neckingeffects, 20) NP-ZnO layers were heated for 1 h at temperatures of 450°C, 500°C, 550°C, 600°C, and 650°C in an electric furnace (HPM-OG, AS ONE Co.), respectively. After the formation of the light-scattering layer, the NP-TiO 2 layer was fabricated onto NP-ZnO layers by the squeegee method.…”
Section: Fabrication Methods Of Np-tco Substratesmentioning
confidence: 99%
“…Considerable efforts, both experimental and theoretical, have been devoted to understand the various physical behaviors of nanoclusters, including the melting and freezing, coalescence or sintering, as well as the deposition on different substrates and so on. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, there is a difficulty in experiments because large numbers of repetitions and attempts are needed due to varying parameters in preparing nanoclusters. Fortunately, molecular dynamics (MD) simulations offer an effective tool for studying properties of nanoclusters and complement ongoing experimental efforts.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 On the other hand, investigations have also indicated that small nanoclusters can coalesce into large spherical or rodlike clusters. 11,14,15,18 Tungsten (W) as well as its alloys and compounds are widely used in national defense, aerospace, electronic engineering, the energy industry, the metallurgical industry and mechanical processing due to their extraordinary physical and thermal properties such as high density and high strength. To date, there have been really limited reports about the melting processes of W nanoclusters.…”
Section: Introductionmentioning
confidence: 99%